Transitioning to Sustainability: The Impact of ESG on Financial Performance in the Post-Soviet EU States - Hansen, Jackie Damkjær; Xie, Zhuyun (International Journal of Economics and Financial Issues, 2025)
This study investigates the impact of Overall ESG and individual Disclosure scores—Environmental, Social, and Governance—on the financial performance of publicly traded companies in Post-Soviet EU states, specifically focusing on Return on Assets (ROA), Return on Equity (ROE), and Return on Investment (ROI) as financial performance indicators. Using a multiple linear regression model and a sample of 245 firms, the research examines how ESG and its components influence financial outcomes while controlling for market capitalization, company age, and R&D expenditure. The findings reveal that neither overall ESG nor individual Disclosure scores significantly affect ROA, ROE, or ROI. Notably, the Environmental Disclosure Score shows a negative but non-significant relationship with financial performance, while the Social and Governance Disclosure Scores also lack statistically significant effects. Conversely, market capitalization positively influences financial performance, and company age negatively impacts ROE and ROI. R&D expenditure does not significantly affect any financial performance measures. These results suggest that ESG disclosures in Post-Soviet EU States, may not yet be sufficiently developed to influence financial performance directly. The study underscores the importance of firm size in driving financial success in the region and emphasizes the need for further research into ESG factors in this context.